Persuasive propaganda during the 2015 Argentine Ballotage - Di Tella, Rafael; Galiani, Sebastian; Schargrodsky, Ernesto (Journal of Comparative Economics, 2021)
•We exploit experimental data to study a State-sponsored propaganda campaign against the opposition candidate during the 2015 Argentine presidential election.•The government used the State monopoly on the TV broadcasting of soccer matches to send messages to a captive audience attacking the opposition candidate.•Exposure to the government propaganda campaign significantly reduced the recipients’ intention to vote for the opposition candidate.The defenses employed by the opposition candidate (a reply to the government accusations, an unrelated positive message, and a counter-attack) did not mitigate the detrimental effect of the government's propaganda campaign.•The campaign's effect is entirely driven by women, who traditionally view less soccer and, thus, had likely less prior exposure to the government “ads”. We study a propaganda campaign sponsored by the Argentine government against the main political challenger in the days preceding the 2015 runoff presidential election. Subjects in the treatment group watched an “ad” that had been aired during soccer transmissions as part of this campaign. They were then asked about their vote intentions. Relative to subjects in the control group, their declared preference for the challenger drops by 6.5 percentage points for a persuasion rate of 11.2%. We find no effects of the three types of defenses employed by the challenger (a positive message unrelated to the “ad”, a reply to the accusations in the “ad”, and a counter-attack). The propaganda effect is driven by women.